Overlimiting current near a nanochannel a new insight using molecular dynamics simulations - D. Manikandan (Nature Portfolio, 2021)
Abstract In this paper, we report for the first time overlimiting current near a nanochannel using all-atom molecular dynamics (MD) simulations. Here, the simulated system consists of a silicon nitride nanochannel integrated with two reservoirs. The reservoirs are filled with $${0.1} \, \hbox {M}$$ 0.1 M potassium chloride (KCl) solution. A total of $${\sim } 1.1$$ ∼ 1.1 million atoms are simulated with a total simulation time of $${\sim } 1 {μ s}$$ ∼ 1 μ s over $${\sim }$$ ∼ 30000 CPU hours using 128 core processors (Intel(R) E5-2670 2.6 GHz Processor). The origin of overlimiting current is found to be due to an increase in chloride ( $${Cl^-}$$ C l - ) ion concentration inside the nanochannel leading to an increase in ionic conductivity. Such effects are seen due to charge redistribution and focusing of the electric field near the interface of the nanochannel and source reservoir. Also, from the MD simulations, we observe that the earlier theoretical and experimental postulations of strong convective vortices resulting in overlimiting current are not the true origin for overlimiting current. Our study may open up new theories for the mechanism of overlimiting current near the nanochannel interconnect devices.